Isolation and identification of Beta-Lactam Producing Microorganisms using PCR based methodologies - Krallis, Myrsini (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1997)
The polymerase chain reaction (PCR) was investigated as a potential tool in microbial screening for 13-lactam. producing organisms. Optimization of PCR conditions and the addition of acetamide to the PCR reaction allowed for the successful amplification of the isopenicillin N synthetase (lPNS) gene in S. clavuligerus, S. tanashiensis, S. griseus, S. olivaceus, S. lipmanii, and S. chartreusis. PCR was used to produce a radiolabelled probe from S. clavuligerus that was used to detect analogous genes in bacteria and fungi. Southern blot and dot blot analysis using the lPNS probe revealed the presence of IPNS-like sequences in seventeen organisms. Fourteen of these sequences belonged to known 13-lactam. producing organisms; one unidentified soil isolate; and two non-/3-lactam. producing organisms viz. S. venezuelae ATCC 10712 and S. hygroscopicus ATCC 21703. The lPNS gene was also detected in a 13-lactam producer (S. chartreusis) that had lost its ability to produce antibiotic. It would therefore have been overlooked in a conventional antibiotic screening program. The use of PCR, coupled with Southern hybridization and dot blot analysis, increased the sensitivity and specificity of the antibiotic screening procedures and allowed for the investigation of evolutionary relationships between the eukaryotes and the prokaryotes. A preliminary investigation into the potential use of RAPD PCR and protein fmgerprinting as tools for solving discrepancies in streptomycete identification was conducted. A variety of streptomycete species that were chosen as being representative of a number of numerical taxonomic classes were amplified using various RAPD primers. Streptomycetes appear to be genetically diverse organisms as was reflected by their RAPD and protein profiles. The application of PCR in an antibiotic screening program showed great potential as a specific and sensitive tool in the detection of /3-lactam producers and in the elimination of duplicate strains.
Keywords: Polymerase chain reaction; Bacterial genetics; Fungi -- Genetics; Beta lactam antibiotics; Microbial enzymes